Korespondencja Zygmunta Haupta z redakcją „Tematów” - Panas, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
Zygmunt Haupt’s preserved correspondence with the editors of Tematy (Paweł Mayewski and Jan Kempka) from the years 1962-1970 consists of seventeen letters. During that time, Haupt published in the quarterly from New York his translations of three poems by Robert Frost and one by Robert Lowell, as well as one short story of his own. This correspondence, although modest in volume, is an interesting testimony of Haupt’s collaboration with an important émigré journal. It also presents the writer as someone interested in the current literary life, trying his hand as a translator of American poetry.